Serological and molecular detection, isolation and characterization of leptospira interrogans from cats in Peninsular Malaysia - Alashraf, Abdulrahman (2020)
Leptospirosis is one of the most common zoonotic diseases worldwide and it has been frequently reported in tropical regions, the annual cases of leptospirosis have exceeded more than one million worldwide with high mortality rates in humans. There is a paucity of data regarding the leptospiral infection in cats. Investigation on leptospiral infection in cats is necessary for further understanding the susceptibility of cats towards Leptospira spp. and to increase the public health awareness. In this study, a total of 192 blood samples were collected from cats from four shelters in Peninsular Malaysia. The sero-detection against Leptospira spp. was as high as 21.3% (n= 41/192). Bataviae was the predominant serogroup found in cats, the antibodies titres ranged from 1:100 to 1:1600. Additionally, the blood, urine and kidneys from 82 cats were tested using PCR and bacterial culture. The results showed that 4.8% cats (n= 4/82) had pathogenic leptospiral DNA in urine and 4.8% cats (n= 4/82) showed positive cultures from urine and/or kidney. The leptospires isolates were identified using serological and molecular methods as pathogenic L. interrogans serogroup Bataviae. Furthermore, 21 cats that were diagnosed positive for Leptospira spp. were proceeded for renal examination. The kidney showed histopathological changes from mild to severe and interstitial nephritis was the most observed lesion, whilst 95.2% cats (n=20/21) were positively stained for lipL32 in the lumen of kidney tubules. The isolated leptospiral strain from this study (Alashraf U53-UPM; MK391605) was proceeded for further genomic analysis. The genome analysis revealed genes involved in pathogeneses, environmental tolerance (pH and temperature resistance) and tissue invasion. Moreover, 99% Average Nucleotide Identity (ANI) similarity was revealed with previously isolated Bataviae strains in rats and humans in Malaysia and Thailand respectively. The current study shows that leptospiral infection is common in cats in Malaysia. Locally and globally, the results provide evidence to improve existing knowledge of leptospiral infection in cats. This study presents the first report of the ability of cats to act as a reservoir harbour the pathogenic Leptospira spp. in kidney and shed the pathogens in urine to environment. The infected cats with leptospires had histopathological changes in kidney with expression of lipL32. The isolated leptospires were pathogenic and closely related to a highly pathogenic Copenhageni strain Fiocruz L1-130. The genome characteristics of the isolates contribute to further comparative analysis of pathogenic leptospiral evolution.